Przesłanki utworzenia terminowego rynku produktów rolnych na giełdzie towarowej w Polsce - Zbaraszewski, Wojciech (Reasons of Creation of Futures Contracts Market of Agricultural Produce at Goods Fair in Poland, 2006)
The article presents a possibility of futures contracts creation of agriculture produce at goods fair in Poland in context of the world experience. Such an aim results from the fact that the market of basic agriculture produce is treated as a strategic one and the risk in agriculture production is a special risk. The article presents legal, market and educational barriers of creation of the futures contracts market.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1109, s. 753-760